2007
DOI: 10.1073/pnas.0611046104
|View full text |Cite
|
Sign up to set email alerts
|

The tiny eukaryote Ostreococcus provides genomic insights into the paradox of plankton speciation

Abstract: The smallest known eukaryotes, at Ϸ1-m diameter, are Ostreococcus tauri and related species of marine phytoplankton. The genome of Ostreococcus lucimarinus has been completed and compared with that of O. tauri. This comparison reveals surprising differences across orthologous chromosomes in the two species from highly syntenic chromosomes in most cases to chromosomes with almost no similarity. Species divergence in these phytoplankton is occurring through multiple mechanisms acting differently on different chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
532
2
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 581 publications
(560 citation statements)
references
References 59 publications
9
532
2
4
Order By: Relevance
“…We found high gene density in the pico-prymnesiophyte metagenome ( Fig. 3A and SI Materials and Methods, Section 7), akin to pico-prasinophytes, which purportedly underwent genome streamlining to optimize life in oligotrophic niches (9,11). GC content was 60%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found high gene density in the pico-prymnesiophyte metagenome ( Fig. 3A and SI Materials and Methods, Section 7), akin to pico-prasinophytes, which purportedly underwent genome streamlining to optimize life in oligotrophic niches (9,11). GC content was 60%.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the importance of eukaryotic phytoplankton to carbon cycling only six genomes have been sequenced and analyzed comparatively, all being from diatoms and prasinophytes. These revealed greater differentiation than anticipated on the basis of 18S rRNA gene analyses (9)(10)(11). The observed genomic divergence is associated with major differences in physiology and niche adaptation (10).…”
mentioning
confidence: 89%
“…The existence of a second vinyl reductase that has low or no homology to DVR was predicted by Nagata et al (2005), and Ito et al (2008) reached a similar conclusion from slr1923. Indeed, the slr1923 (cvrA) homolog was found in other cyanobacteria, in the red alga C. merolae (Matsuzaki et al, 2004), in the diatom T. pseudonana (Armbrust et al, 2004), and in the green algae O. lucimarinus (Palenik et al, 2007) and C. reinhardtii. The deduced amino acid sequences of the homologues of Slr1923 have no homology to that of DVR.…”
Section: Discussionmentioning
confidence: 99%
“…The significance of the presence of two copies in G. violaceus is not clear at the moment. It was found that the homolog is present not only in cyanobacteria but also in eukaryotic algae such as the red alga C. merolae 10D (CMJ076C; Matsuzaki et al, 2004), a diatom, Thalassiosira pseudonana CMP 1335 (gw1.2.195.1; Armbrust et al, 2004), and the green algae Ostreococcus lucimarinus (OSTLU_36251; Palenik et al, 2007) and Chlamydomonas reinhardtii (CHLRE-DRAFT_106754). Surprisingly, it is also found in land plants such as Arabidopsis (AT1G04620) and rice (Oryza sativa; 4335472).…”
Section: Phylogenetic Analysis Of Slr1923 Homologues and Their Distrimentioning
confidence: 99%
“…MS024-2A (Woyke et al, 2009) and eubacterium SCB49 (Yooseph et al, 2010). Ostreococcus (Derelle et al, 2006;Palenik et al, 2007) and Micromonas (Worden et al, 2009) were among the most abundant picoeukaryotes identified in annotated proteincoding transcripts, but rRNA-based analysis suggests a large diversity of eukaryotes without sequenced genomes were present in the samples.…”
Section: Metatranscriptomic Analysis Of Montereymentioning
confidence: 99%